PERAN PERGURUAN TINGGI DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Nor Aishah Buang (Pascasarjana IAIN Metro, 2016)
Education is one of important field in changing someone life status and produce the economic country. In globalization era, the deep and comprehensive researches especially in developmental of high education are required for education transformation toward economy-knowledge based. The investment in education sector and expand the skilled job opportunity become the prior policy in ASEAN countries to develop economic site. Collage institution has the main role not only in creating societies who have high education but also the skilled societies who can fulfill the labor market requirement. The aim of this research is to investigate the role of collage institution in facing ASEAN Economic Society (MEA) through the harmonization between education and economic society prosperity. MEA covered the skilled labor market consist of 10 countries in each country has different education system based on their economic, social, culture, and political. The explanation found that the lack of standard systems for entire ASEAN countries develop the big challenge faced by MEA to penetrate the market of skilled labor in Southeast Asia.